HOSPITAL ACQUIRED INFECTIONS. A SCIENTIFIC REVIEW OF EVIDENCE BASED RECOMMENDATIONS. - Khalid Eid Madi Alahmadi, Khalid Hussain Alfaifi, Anwar Mohammed Hemaid Alsalmi, Abeerah Khalid Abdulqader Albokhari, Nisreen Mohammed Omar Helmi, Atheer Fahad Sanad Alshaikh, Mohammed Abdulrazzag M Hawsawi, Faysal Abdullah Hamdi Aman; Firas Fawaz Anwar Felemban, Anas Fawaz Anwar Felemban, Ali Hassan Omar Al Gefri (Chelonian Research Foundation, 2023)
Hospital-acquired infections can increase the rate of morbidity and mortality as well as medical costs. Nosocomial infection is spread in various ways, such as surgical, intravenous catheters, surface contact (like hands), and also through the air. Some interventions, including appropriate hand and surface decontamination, sufficient staffing, improved ventilator management, and the use of coated central venous and urinary catheters, have all been linked with a considerably lower rate of nosocomial infection. Multiple interventions simultaneously are required for comprehensive infection control, and multiple actions may have a better outcome than a single action. Some multiple infection control protocols will possibly show a more effective result than employing a single or few strategies. Several non-pharmacological interventions to prevent HAIs will reduce the requirement for prolonged or multiple-drug antibiotic courses for infected patients. And lower antibiotic usage will decrease the risk of antibiotic-resistant organisms and may improve the effectiveness of antibiotic therapy for patients with acquired infections. Keywords: hospital-acquired infection, health-care-associated infection,nosocomial infection, infection control, hand washing,